Well-defined Z-scheme Na2Ti3O7/Ag/CdS multidimensional heterojunctions with enhanced H2 production from seawater under visible light. (19th August 2022) - Xiong, Ge; Shen, Shuling; Xiao, Shuning; Cai, Cong; Zhang, Pengfei; Tang, Zhihong; Li, Jing; Yang, Junhe
Abstract: Production of H2 from photocatalytic seawater splitting is a more promising but more difficult way than from pure water due to the high salinity of seawater. Efficient and stable photocatalyst is crucial and desired. In this work, well-defined Z-scheme Na2 Ti3 O7 /Ag/CdS (N10 A1 C5 ) multidimensional heterojunctions composed of zero-dimensional Ag nanoclusters, one-dimensional Na2 Ti3 O7 (NTO) nanotubes, and two-dimensional CdS nanoplates were constructed. Zero-dimensional Ag nanoclusters decorated on the surface of NTO nanotubes not only act as electron mediator for the formation of Z-scheme between NTO and CdS, but also provide hot electrons due to their plasma effect. CdS nanoplates cooperated with Ag nanoclusters act as visible light absorber, which improve both the visible light absorption range and intensity. With Na2 S·9H2 O (0.25 M) and Na2 SO3 (0.35 M) as the sacrificial agent, the resultant Z-scheme N10 A1 C5 heterojunctions show a H2 production of 1793 μmol/(g·h) from visible-light-driven photocatalytic seawater splitting, which is 9.7 times that of NTO/CdS type II heterojunctions. Notably, the Z-scheme N10 A1 C5 also exhibit stability of structure in the high salinity environment due to the interlayer structure of NTO, which can accommodate metal cations in seawater. After four 3-h cycles, the catalytic activity can still maintain 96.6%. This Z-scheme heterojunction is expected to provide a strategy for the design of efficient and stable photocatalysts for the solar energy driven seawater splitting. Graphical abstract: Image 1 Highlights: Ag induces the formation of Z-scheme Na2 Ti3 O7 /Ag/CdS heterojunctions. Ag nanoclusters both acts as electron mediators and provides hot electrons. Na2 Ti3 O7 /Ag/CdS exhibits enhanced photocatalytic H2 production from seawater.